Application of IoT for Filling and Monitoring Water Tanks Using NodeMCU ESP8266 and MQTT Protocol - M. Ramaddan Julianti; Detin Sofia; Aldian Ridho Kusuma (Institut Teknologi dan Bisnis Bina Sarana Global, 2022)
In this research, a system has been designed that aims to prevent water wastage every time you fill a water reservoir. The design of the system is in the form of filling and monitoring automatic water reservoirs that go through 5 stages, namely tool prototype design, prototype making, making a series of tools, measuring and analyzing data. This tool utilizes the HC-SR04 sensor which will detect the water level in the water reservoir if the water level is 1-23 cm then the water reservoir is filled automatically and when the sensor distance from the water is 20 cm then the water reservoir will not be refilled. In designing this system using a NodeMCU ESP8266 microcontroller and the MQTT protocol which will run the control process on the system and process input data from sensors. The output will be displayed on the LCD (Liquid Crystal Display), MQTT Dash and Node-Red Dashboard in the form of the water level in the reservoir. The added relay functions as an automatic switch when turning off and turning on the water flowing in the reservoir. This can reduce the use of water as a medium for ablution that is wasted so that it becomes more effective and efficient.